G569(P) Extubations – how common are unplanned extubations in extremely preterm infants?. (27th April 2016) - Osmulikevici, O; Chong, D; Colledge, N; Paterson, K; Ramaiah, S
Abstract : Context: The aim of this project was to determine the frequency and characteristics of unplanned extubations in preterm infants in a tertiary Neonatal Unit. Problem: There was a perception that there is a relatively large proportion of unplanned extubation events in infants born ≤28 weeks gestation and also that the incidence in our unit was higher compared to the published literature. Assessment of problem and analysis of its causes: Potential causes are challenges met when fixating the endotracheal tube to a very small person, mostly the size of the fixation tool and its interaction with fragile skin. There is no clear evidence for the use of sedation in extreme preterm infants for short term ventilation. The implications of unplanned extubations are potential harm to babies, increased work load for staff, increased levels of parental anxiety. Intervention: An audit was designed to measure the frequency and characteristics of unplanned extubations in infants born less than 28 weeks gestation, with an intention to develop a care package to decrease their incidence. Study design: The study included ventilated babies born ≤ 28 week's gestation between January 2015–April 2015. Any extubation events documented in the nursing or medical records were included. Extubation events were classified as planned – if clearly documented as 'planned' by the clinical team, and 'unplanned' if were unexpected, accidental, tube dislodged or blocked. Strategy for change: The nursing staff was involved from the beginning. Findings were presented in the Department Clinical Governance meeting. A core group was formed to develop a care package with the intention to reduce the frequency of unplanned extubation events in the Neonatal Unit. The care package consisted in the development of a sticker and intubation chart, used to monitor the endotracheal tube position and the number of intubation events in a certain baby. The care package was shared to nurses, junior doctors and consultants for implementation. Results: 104 extubation events were recorded from 39 infants during the study period, 1 extubation event/100 hrs (4.1 days). There were a total of 9963 h of ventilation during the study period. Median ventilation days of 225 h (10.6 days) per baby. Planned events: 63, 1 event/158 h (6.5 days) and unplanned: 41 events, 1 event/243 h (10.1 days). Median number of unplanned extubation events per infant was 6 for infants born ≤25 weeks and 2 for infants born ≥25 weeks gestation. Most common cause reported as a reason for unplanned extubation was 'self extubation'. 65% of the unplanned extubation events needed re-intubation. It was noted that there was no clear guidance with regards to fixation or checking the endotracheal tube position. Measurement of improvement: We are planning a re-audit of the unplanned extubation events after 6 months into the implementation of the care package. Effects of changes: We know from similar intervention elsewhere that this approach decreases the incidence of unwanted events. The process of endotracheal tube checking by the nursing staff twice a day, documenting its position and a clear display of number of extubations at the cot side with discussions around it, acts as a powerful tool to decrease the incidence of unplanned extubations. Lessons learnt: To bring a 'change in practice' is difficult, however with involvement of key team players it is possible to achieve the expected outcome! Message for others: 'Impossible is possible!'